Measuring the willingness to share personal health information: a systematic review - Benevento, Marcello; Mandarelli, Gabriele; Carravetta, Francesco; Ferorelli, Davide; Caterino, Cristina; Nicolì, Simona; Massari, Antonella; Solarino, Biagio (Frontiers in Public Health, 2023)
Background In the age of digitalization and big data, personal health information is a key resource for health care and clinical research. This study aimed to analyze the determinants and describe the measurement of the willingness to disclose personal health information. Methods The study conducted a systematic review of articles assessing willingness to share personal health information as a primary or secondary outcome. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis protocol. English and Italian peer-reviewed research articles were included with no restrictions for publication years. Findings were narratively synthesized. Results The search strategy found 1,087 papers, 89 of which passed the screening for title and abstract and the full-text assessment. Conclusion No validated measurement tool has been developed for willingness to share personal health information. The reviewed papers measured it through surveys, interviews, and questionnaires, which were mutually incomparable. The secondary use of data was the most important determinant of willingness to share, whereas clinical and socioeconomic variables had a slight effect. The main concern discouraging data sharing was privacy, although good data anonymization and the high perceived benefits of sharing may overcome this issue.